Growing, grown, gone. The ephemeral status of pets among the Madiha (Kulina) of the Peruvian Amazon - Andrea Zuppi (Journal de la Société des Américanistes)
The Madiha, a people of southwestern Amazonia, raise as pets the younglings of the animals they kill during the hunt. This article emphasizes two aspects of pet keeping among the Madiha: (i) the fragility and temporary nature of the taming process and (ii) the role that pet keeping plays in the social fabrication of infants and children. By analyzing pet keeping practices against notions of mastery/ownership, feeding and child adoption, as well as by drawing on the work of specialists of the region, this article shows that pet keeping does not have as its purpose the creation of an adult animal, nor can it unproblematically be considered under the prism of adoption since the animals kept as pets are inevitably de-familiarized.